Piezosurgery versus conventional rotary surgery for impacted third molars: A randomised, split-mouth, clinical pilot trial - DEMİRCİ, AHMET; DERGİN, GÜHAN; BAYRAM, FERİT (My University, 2023)
Background: Few studies have compared the effects of piezosurgery and conventional rotary surgery for impacted wisdom teeth on the quality of life. Among these studies, the inclusion parameters and evaluation methods have varied.Material and Methods: This study aimed to compare the effects of piezosurgery and conventional rotary in- struments on the quality of life using a standardised method. Patients with bilateral and symmetric mandibular impacted wisdom teeth were included based on the Winter and Pell-Gregory scale and Yuasa difficulty index criteria. The primary objective was to assess the effects of the methods on the quality of life using the Oral Health Impact Profile-14 questionnaire. Secondary objectives included comparisons of swelling, trismus, pain, and total operative times. The study was conducted between October 2021 and March 2022. The clinical trial protocol was recorded in the United States National Library of Medicine clinical trial registry (NCT05545553). Results: We enrolled 20 patients (40 wisdom teeth) and found that the removal of impacted teeth using the piezo- surgery method positively affected the quality of life and considerably improved swelling, trismus, and pain scores. However, piezosurgery may affect postoperative morbidities such as increased total operative times. Conclusions: Piezosurgery appears to have advantages over conventional rotary surgery for impacted wisdom tooth extraction in terms of quality of life and postoperative symptoms. However, further research should inves- tigate potential drawbacks and confirm these findings
Keywords: Diş Hekimliği; Klinik Bilimler; Ağız, Diş-Çene Hastalıkları ve Cerrahisi; Sağlık Bilimleri; Dentistry; Clinical Sciences; Oral, Maxillofacial and Surgery; Health Sciences; Klinik Tıp (MED); Klinik Tıp; DİŞ HEKİMLİĞİ, ORAL CERRAHİ VE TIP; Clinical Medicine (MED); CLINICAL MEDICINE; DENTISTRY, ORAL SURGERY & MEDICINE; Periodontoloji; Ortodonti; Ağız Cerrahisi; Diş Hijyeni; Dişçilik Hizmetleri; Diş Hekimliği (çeşitli); Periodontics; Orthodontics; Oral Surgery; Dental Hygiene; Dental Assisting; Dentistry (miscellaneous); General Dentistry